Thermoelasticity without energy dissipation for initially stressed bodies - Jun Wang; Susan Palmer Slattery (International Journal of Mathematics and Mathematical Sciences)
Thermoelastic equations without energy dissipation are formulated for a body which has previously received a large deformation and is at nonuniform temperature. A linear theory of thermoelasticity without energy dissipation for prestressed bodies is derived and the uniqueness theorem for a class of mixed initial-boundary value problems is established.